PENERAPAN CIRCULAR ECONOMY SEBAGAI STRATEGI TRANSFORMASI EKONOMI PETANI TRADISIONAL DALAM KASUS BANK SAMPAH MALANG - Hilmi Arifudin, Muhamad (Journal of Economics and Regional Science, 2026)
The urgency of implementing circular economy is getting higher as the global environmental crisis increases and economic stagnation in the traditional agricultural sector. This article aims to examine the potential integration of the Waste Bank model in the economic transformation strategy of traditional farmers through a circular economy approach. This research uses descriptive qualitative method based on literature study with conceptual and empirical literature analysis approach. The results show that the circular economy model through the Waste Bank can transform organic waste into productive resources such as compost and alternative animal feed, which contributes to an increase in farmers' income by up to 22%. However, significant challenges are still faced, such as low ecological literacy, limited waste processing technology, and weak local institutional synergies. This research contributes to community-based policy development and reinforces the relevance of circular economy in the agrarian sector. The conclusion suggests the need for affirmative regulations, infrastructure support, and cross-sector collaboration to strengthen the sustainable adoption of circular economy models at the village level